2021
DOI: 10.1144/jgs2021-039
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ostracod communities throughout the Mulde/ lundgreni event: contrasting patterns of species richness and palaeocommunity compositional change

Abstract: The Mulde event was one of several significant turnover events during the Silurian. This event is mostly recognized in the fossil record of graptolites and conodonts, as well as stable carbon isotopic data. Therefore, the ostracods – a significant part of the benthos – comprise a new and important dimension in understanding this global geobiological episode. Here, a new ostracod and δ 13C high-resolution record from the upper Wenlock interval from a Gėluva-118 core (central Lithuania) are presented. Analyses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The stable carbon isotope composition was analyzed using traditional techniques (e.g. Rinkevičiūtė et al 2021) by the Thermo Gasbench II in tandem with the Thermo Delta V isotope ratio mass spectrometer at the Nuclear Research Department of the State Research Institute Center for Physical Sciences and Technology, Vilnius, Lithuania. All samples were loaded into 10 mL Labco Exetainer vials, flushed with He, and later treated with 99.99% H 3 PO 4 at 50 °C for 10 h.…”
Section: Methodsmentioning
confidence: 99%
“…The stable carbon isotope composition was analyzed using traditional techniques (e.g. Rinkevičiūtė et al 2021) by the Thermo Gasbench II in tandem with the Thermo Delta V isotope ratio mass spectrometer at the Nuclear Research Department of the State Research Institute Center for Physical Sciences and Technology, Vilnius, Lithuania. All samples were loaded into 10 mL Labco Exetainer vials, flushed with He, and later treated with 99.99% H 3 PO 4 at 50 °C for 10 h.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the best examples relevant for the establishment of the picture of hierarchical emergence and persistence of geobiomes come from studies of Paleozoic marine faunas or of so-called coordinated stasis of multiple lineages and community patterns (Brett and Baird 1995;Brett et al 1996).The majority of lineages formed recurring communities, and the taxonomic and ecological turnover was concentrated within relatively short periods of time (Ivany et al 2009). The application of dynamical systems tools to Silurian Period faunas revealed that the patterns of species dominance were modulated by oceanic circulation and sea-level states and sharp transitions between them (Spiridonov et al 2015(Spiridonov et al , 2016(Spiridonov et al , 2017a(Spiridonov et al ,b, 2020bVenckutė-Aleksienė et al 2016;Spiridonov 2017;Crampton et al 2018;Whittingham et al 2020), with a pattern showing coherence in space (Spiridonov et al 2020a) and repeating itself at several time scales (Rinkevičiūtė et al 2022). The spatial evolutionary processes are modulated by sea-level change, climate, and tectonic perturbations-these factors play a crucial role in modulating diversity at large temporal and spatial scales (Lieberman and Eldredge 1996;Lieberman 2003;Radzevičius et al 2016;Stigall et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…2012), a severe, although short-lived, biodiversity disturbance detected in the fossil record of Baltic ostracods (Rinkevičiutė et al . 2021) and graptolites (Urbanek et al . 2012).…”
mentioning
confidence: 99%